alpha-Synuclein: a Modulator During Inflammatory CNS Demyelination - Kuhbandner, Kristina; Hoffmann, Alana; Alvarado, Maria Nazareth; Seyler, Lisa; Bäuerle, Tobias; Winkler, Jürgen; Linker, Ralf (Journal of Molecular Neuroscience, 2020)
Neuroinflammation and demyelination are hallmarks of several neurological disorders such as multiple sclerosis and multiple system atrophy. To better understand the underlying mechanisms of de- and regeneration in respective diseases, it is critical to identify factors modulating these processes. One candidate factor is alpha-Synuclein (aSyn), which is known to be involved in the pathology of various neurodegenerative diseases. Recently, we have shown that aSyn is involved in the modulation of peripheral immune responses during acute neuroinflammatory processes. In the present study, the effect of aSyn deficiency on de- and regenerative events in the CNS was analyzed by using two different demyelinating animal models: chronic MOG(35-55)-induced experimental autoimmune encephalomyelitis (EAE) and the cuprizone model. Histopathological analysis of spinal cord cross sections 8 weeks after EAE induction revealed a significant reduction of CNS inflammation accompanied by decreased myelin loss during late-stage inflammatory demyelination in aSyn-deficient mice. In contrast, after cuprizone-induced demyelination or remyelination following withdrawal of cuprizone, myelination and neuroinflammatory patterns were not affected by aSyn deficiency. These data provide further evidence for aSyn as regulator of peripheral immune responses under neuroinflammatory conditions, thereby also modulating degenerative events in late-stage demyelinating disease.
CRIS-Team WoS Importer:2020-04-07